2010
DOI: 10.1007/s12559-010-9069-9
|View full text |Cite
|
Sign up to set email alerts
|

If Visual Saliency Predicts Search, Then Why? Evidence from Normal and Gaze-Contingent Search Tasks in Natural Scenes

Abstract: The Itti and Koch (Vision Research 40: 1489-1506, 2000 saliency map model has inspired a wealth of research testing the claim that bottom-up saliency determines the placement of eye fixations in natural scenes. Although saliency seems to correlate with (although not necessarily cause) fixation in free-viewing or encoding tasks, it has been suggested that visual saliency can be overridden in a search task, with saccades being planned on the basis of target features, rather than being captured by saliency. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
1
24
2
Order By: Relevance
“…Our results add to what has already been learned about the sorts of contextual cues that configural or gist information might provide for search in natural scenes (Foulsham & Underwood, 2011;Henderson, 2003;Vo & Henderson, 2010). Building this contextual information (e.g.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our results add to what has already been learned about the sorts of contextual cues that configural or gist information might provide for search in natural scenes (Foulsham & Underwood, 2011;Henderson, 2003;Vo & Henderson, 2010). Building this contextual information (e.g.…”
Section: Discussionsupporting
confidence: 78%
“…Previous work has demonstrated that the effects of saliency on search are minimal (Chen & Zelinsky, 2006;Foulsham & Underwood, 2007), and the implication of this research is that when we search, what we know about the target and the scene overrides any bias to look at conspicuous items. Where saliency is predictive of search, it is likely because saliency coincides with other properties of the target that make it easier to find, such as ease with which its location can be predicted in a scene (Foulsham & Underwood, 2011). In the present research, we found that there was almost no correlation between saliency and the time taken to move the eyes to a target in normal scenes.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Now, imagine a person looking at an advertisement for a zoo at a distant billboard that shows a tiger, a lion, a giraffe, a rhinoceros, and an elephant, all in close proximity to each other and within the person's span of attention [20][21][22]. A distributed representation system would have to process each animal separately, one after the other, in order to recognize them.…”
Section: A Theoretical Perspective: On the Need For Simultaneous Actimentioning
confidence: 99%